New ICT and technology dissemination models for achieving better farmer-scientist interface - Singh, A K; Singh, Randhir; Gowda, M J Chandre; Meera, Sheikh N (Indian Farming, 2021)
ICTs continue to gain popularity and offer unique opportunities to share information among large number of farmers and other stakeholders. While not a panacea for all of the problems facing extension, the integration of ICTs as a communication channel is potentially reaching millions of farmers and as an enabler of change is considered a critical part of future reform and investment agendas. Using ICT to achieve agricultural development goals requires supplementary investments, resources, and strategies. The attractiveness of the newest ICTs can lead to a preference for the latest technologies at the expense of older technologies (such as radio), yet the newest, most elaborate, or most innovative technology is not automatically the most appropriate one. An innovative mix of technologies, for instance, radio programs with a call-in or SMS facility for feedback, can also be a cost-effective solution.